EVALUASI KEGIATAN LITERASI DI SEKOLAH DASAR NEGERI KECAMATAN TANJUNG RAJA KABUPATEN OGAN ILIR - Lisa Mandasari (Adisam Publisher, 2024)
This study aims to determine the results of the evaluation of the Implementation of Literacy Activities in the Public Elementary School of Tanjung Raja District, Ogan Ilir Regency. This research is a descriptive study with a qualitative approach. Data that is used based on its type is quantitative data and qualitative data while based on the source are primary data and secondary data. Data collection instruments used were observation, interviews and documentation. The informants in this study were the Head of the Technical Implementation Unit (UPT) of the Education Office in Tanjung Raja District, Ogan Ilir Regency; Head of Public Elementary School in Tanjung Raja District, Ogan Ilir Regency; Public Elementary School teacher in Tanjung Raja District, Ogan Ilir Regency; State Elementary School students in Tanjung Raja District, Ogan Ilir Regency. Data analysis is a qualitative analysis with an interactive model. Based on the results of the study note that Literacy Activities in the Elementary School of the District of Tanjung Raja, Ogan Ilir District have been carried out, although not yet maximally.